The use of blood flow restriction does not enhance adaptations of corticospinal excitability or intracortical inhibition after acute resistance training - Martin Keller; Fabio Ruch; Christoph Centner; Faude Oliver (Bern Open Publishing, 2023)
Resistance exercise with blood flow restriction (BFR) is considered a safe and powerful training tool. Low-load (LL) resistance training with BFR results in comparable hypertrophy compared to conventional heavy-load (HL) resistance training (Centner et al., 2019). Additionally, LL training with BFR (LL-BFR) induces comparable (Grønfeldt et al., 2020) or slightly lower (Centner et al., 2019) effects on muscle strength than HL training. It is generally accepted that increases in maximum strength are mediated by muscular hypertrophy and/or neural adaptations. However, the effect of BFR on neural adaptations is scarcely investigated. The aim of this study was therefore to investigate the effects of BFR on acute neural adaptations following a single bout of resistance training. Fifteen male participants (21-35 years) volunteered to participate in this study. On three separate days, participants performed a strength training session of the right elbow flexors with either LL, LL-BFR or HL. Neuromuscular adaptations were investigated before and after each resistance training session by means of transcranial magnetic stimulation (single- and paired-pulse TMS) and peripheral nerve stimulation (Mmax). Data were acquired during submaximal sustained isometric contractions. During LL-BFR, the cuff was inflated to 50% of the individual arterial occlusion pressure to restrict venous outflow in the working musculature during exercise. The preliminary data analysis with mixed linear models revealed that, compared to baseline values, normalized MEPs (% of Mmax) from the trained biceps brachii were enhanced for HL (Cohen's d = 0.51) but not LL-BFR (Cohen's d = 0.03) when compared to LL. None of the groups showed relevant changes in short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF). The size of Mmax decreased slightly for HL (Cohen's d = -0.18) but not LL-BFR (Cohen's d = 0.06) when compared to LL. This is the first study that investigated acute neural adaptations in response to resistance training with and without BFR. We observed increased MEP amplitudes after HL but not LL what is in line with previous evidence (Mason et al., 2019). Since training with BFR results in a rapid increase in motoneuronal excitability (Copithorne et al., 2020), the increased MEP are less likely caused by changes at the cortical site. Centner, C., Wiegel, P., Gollhofer, A., & König, D. (2019). Effects of blood flow restriction training on muscular strength and hypertrophy in older individuals: A systematic review and meta-analysis. Sports Medicine, 49, 95-108. https://doi.org/10.1007/s40279-018-0994-1 Copithorne, D. B., Rice, C. L., & McNeil, C. J. (2020). Effect of blood flow occlusion on corticospinal excitability during sustained low-intensity isometric elbow flexion. Journal of Neurophysiology, 123(3), 1113-1119. https://doi.org/10.1152/jn.00644.2019 Grønfeldt, B. M., Lindberg Nielsen, J., Mieritz, R. M., Lund, H., & Aagaard, P. (2020). Effect of blood-flow restricted vs heavy-load strength training on muscle strength: Systematic review and meta-analysis. Scandinavian Journal of Medicine & Science in Sports, 30(5), 837-848. https://doi.org/10.1111/sms.13632 Mason, J., Howatson, G., Frazer, A. K., Pearce, A. J., Jaberzadeh, S., Avela, J., & Kidgell, D. J. (2019). Modulation of intracortical inhibition and excitation in agonist and antagonist muscles following acute strength training. European Journal of Applied Physiology, 119, 2185-2199. https://doi.org/10.1007/s00421-019-04203-9